2004
DOI: 10.1002/we.129
|View full text |Cite
|
Sign up to set email alerts
|

3D Navier–Stokes computations of a stall‐regulated wind turbine

Abstract: Several 2D and 3D Navier-Stokes computations performed with the compressible elsA solver, developed at ONERA, on the wind turbine tested by NREL in the NASA Ames large wind tunnel are presented. After a brief description of the tools and methods used, the predictions of the S809 aerofoil performance are first discussed. Full 3D computations are then presented, analysed and compared with the experimental results. The successes and failures of the computations are highlighted and explained. The analysis focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 13 publications
2
64
0
2
Order By: Relevance
“…In particular, the considered operating point revealed a blade shedding frequency corresponding to the fifth harmonic. This harmonic order is coherent with the results of previous CFD computations of the NREL Phase VI (Le Pape and Lecanu 2004;Li 2014). Regarding the blade-tower alignment event, loads fluctuation relative amplitudes of 1 % for the rotor thrust and 2 % for the mechanical power were computed.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, the considered operating point revealed a blade shedding frequency corresponding to the fifth harmonic. This harmonic order is coherent with the results of previous CFD computations of the NREL Phase VI (Le Pape and Lecanu 2004;Li 2014). Regarding the blade-tower alignment event, loads fluctuation relative amplitudes of 1 % for the rotor thrust and 2 % for the mechanical power were computed.…”
Section: Discussionsupporting
confidence: 89%
“…The turbulence in the boundary layer is modelled by means of the k − ω shear-stress transport (SST) model proposed by Menter (1993). This model has been proved to be suitable for the simulation of wind turbine blades (Bechmann et al, 2011;Johansen and Sørensen, 2004;Le Pape and Lecanu, 2004;Sørensen et al, 2002). However, the implicit assumption of fully turbulent flow might be a source of uncertainty since the existence of laminar-to-turbulent transition can not be completely ruled out.…”
Section: Numerical Methods and Computational Meshmentioning
confidence: 99%
“…The hub and nacelle geometries are disregarded in order to keep the mesh as simple as possible. This approach, which is based on the assumption that the hub and nacelle do not influence substantially the blade root flow, is usually followed when structured meshes are used for simulating wind turbine blades (Johansen et al, 2002;Sørensen et al, 2002;Le Pape and Lecanu, 2004;Schreck et al, 2007;Bechmann et al, 2011). The mesh exploits the symmetry of the rotor by modelling only one half of it and using periodic boundary conditions.…”
Section: Numerical Methods and Computational Meshmentioning
confidence: 99%
“…He showed significant differences in lift behaviour only at the station farthest inboard on the blade. In Other experimental and numerical studies, Tangler (2004) Le Pape and Lecanu (2004) assumed that 3D effects yield delayed stall (separation nearer the trailing edge for a rotational airfoil) with Cl higher than 2D near the blade root location. Timmer and van Rooij (2003) showed that after stall, the values of Cl and Cd depends on the airfoil's leading edge thickness.…”
Section: Literature Surveymentioning
confidence: 99%